Any empire - Powell, Nate 1978- (Top Shelf Productions, 2011)
His new book, Any Empire, is a vivid examination of war and violence, and their trickle-down effects on middle America. First, a group of small-town kids find themselves bound together by geography, boredom, and a string of mysterious turtle mutilations. Years later, with Army tanks rolling through the streets of their hometown, these young adults are forced to confront painful questions of privilege, duty, betrayal, and courage